“The Yak”—A remarkable animal living in a harsh environment: An overview of its feeding, growth, production performance, and contribution to food security - Shah, Ali Mujtaba; Bano, Iqra; Qazi, Izhar Hyder; Matra, Maharach; Wanapat, Metha (Frontiers in Veterinary Science, 2023)
Yaks play an important role in the livelihood of the people of the Qinghai-Tibet Plateau (QTP) and remarkably contribute to the economy of the different countries. The yaks are commonly raised at about 3000-5400 m high altitudes above sea level. They provide a number of important products namely milk, meat, fur, manure, as well as the social-status-quo etc. The yaks were domesticated from the wild yaks and are present in the remote mountains of the Qinghai region. In the summer season when higher quantity of pasture is available in the mountain region, the yaks use their long tongue to graze the pasture and in the summer season, they spend about 30-80% of their daytime grazing and the remaining time for walking, resting, and for other activities. In the winter season due to heavy snowfall in the mountains, pasture is scarce, and the yaks face feeding issue due to pasture scarcity, hence, the normal body weight of the yaks are affected and growth retardation occurred, and consequently affects their production performance. In this review article, we have discussed the domestication of the yaks, the feeding pattern of the yaks, the difference between the normal and growth retarded yaks, and also the microbial community and their influences. In addition, blood biochemistry, the compositions of the Yak milk and meat, and reproduction are reported herein. Evidences suggested that the yaks play an important role in the daily life of the people living on the Qinghai Plateau by using milk, meat, fur, and manure for fuel and land fertilizer purposes, as well as, the use for transportation. Their close-associations with the well-being and livelihood have been extensively enormous.